A study of temperature effects on car coated substrate in laser paint removal - Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Azhar Abdul Rahman (2014)
Cynosure Cynergy Pulse Nd:YAG laser was used to remove the painted material of 54 car coated substrate samples A, B and C by manipulating the laser fluence energy (F), pulse width (PW), repetition rate (RR) and beam size (BS). Alicona IFM G4 was used to analyze irradiated crater depths and obtained the optical surface micrograph which provides a pattern of graphical illustration of the removal process. Average temperature (ΔTAV) of car metal substrate was determined during the laser paint removal process by using TC 6621 thermocouple. The maximum ΔTAV ( 0C) reached were 30.36 and 34.89 with BS 3 mm and 5 mm for sample A, 30.25 and 32.6 with BS 3 mm and 5 mm for sample B whereas 28.16 and 33.15 with BS 3 mm and 5 mm for sample C.